Health-related quality of life and associated factors among children with Transfusion-dependent β-thalassaemia: a cross-sectional study in Guangxi Province - Jingyi Qiao; Bingxing Luo; Jian Ming; Xinhua Zhang; Junling Weng; Qingwen Deng; Shanyan Zhou; Yingyao Chen (Health and Quality of Life Outcomes)
Abstract Background Transfusion-dependent β-thalassemia (TDT) is a severe inherited disorder. Without regular treatment, patients with TDT experience complications that can significantly shorten life expectancy and severely impact both their quality of life and that of their families. The condition has attracted significant attention in global health discussions. Due to the challenges of blood supply shortages, the high costs of iron chelation therapy, and hematopoietic stem cell transplantation (HSCT), TDT presents a serious health risk to patients and imposes a substantial burden on families and society. However, research on the health-related quality of life (HRQoL) of thalassemia patients in China remains limited. This study evaluated the factors affecting the HRQoL of these patients, with the goal of developing strategies to improve their quality of life. Methods In this cross-sectional study, children with TDT were recruited from five treatment centers in Guangxi, a province with a high prevalence of thalassemia in China. Structured questionnaires were employed to gather relevant data on sociodemographic variables, disease characteristics, treatments, and associated costs. The HRQoL was assessed using the Transfusion-Dependent Quality of Life (TranQoL) questionnaire, with a proxy version for patients aged 0–11 years and a child version for those aged 12–18 years. Results The study included 418 participants, yielding an overall TranQoL score of 60.6 ± 16.3 among thalassemia patients. Multiple linear regression analysis revealed a negative correlation (P < 0.05) between overall TranQoL scores and several factors: increasing patient age, the presence of multiple thalassemia patients within a family, and undergoing HSCT. Conversely, adherence to regular treatment was positively correlated with higher TranQoL scores (P < 0.05). Conclusion The study demonstrates that HRQoL among Chinese patients with TDT is at a low level. Age, treatment adherence, family support, and socioeconomic status were identified as key determinants influencing HRQoL. It is essential to further enhance and optimize health insurance policies and medical services to support comprehensive treatment strategies for these patients.